2010
DOI: 10.1007/s12020-010-9355-z
|View full text |Cite
|
Sign up to set email alerts
|

Change in amputation predictors in diabetic foot disease: effect of multidisciplinary approach

Abstract: Diabetic foot disease causes important morbidity in diabetic population, and amputation due to diabetic foot disease occurs more often than in general population. We have been evaluating patients with diabetic foot disease in a multidisciplinary approach since year 2000. In the current study, we sought to investigate the change in amputation rate and its predictors in diabetic foot with a multidisciplinary team approach. Seventy-four patients (52 male, 22 female) hospitalised between January 2002 and December … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 21 publications
1
32
0
5
Order By: Relevance
“…Management is best achieved with a multidisciplinary team approach (13,14). At least 40% of amputations in diabetic patients can be prevented with a team approach to wound care (15).…”
Section: Introductionmentioning
confidence: 99%
“…Management is best achieved with a multidisciplinary team approach (13,14). At least 40% of amputations in diabetic patients can be prevented with a team approach to wound care (15).…”
Section: Introductionmentioning
confidence: 99%
“…Every individual risk factor requires accurate identification and management and represents a fundamental task for any multidisciplinary wound center to encourage [124]. Investing healing as the primary endpoint in care acts as a real benchmark for all collective therapeutic efforts [57,87,124].…”
Section: The Essential Role Of Multidisciplinary Approach In Ischemicmentioning
confidence: 99%
“…Investing healing as the primary endpoint in care acts as a real benchmark for all collective therapeutic efforts [57,87,124].…”
Section: The Essential Role Of Multidisciplinary Approach In Ischemicmentioning
confidence: 99%
“…Indeed, solving this problem requires close collaboration among health system and people to develop national and international strategies and interactions with the other health team members. To date, several studies have shown that a multidisciplinary team can reduce amputation rates, save costs and lead to better quality of life in patients with DFU (13)(14)(15)(16). The results of a study conducted by a multidisciplinary healthcare team, established for 10 years on patients with DFU in Sao Paulo, Brazil, showed that this approach decreased the number of yearly amputations and re-ulcerations as well as prolonged hospitalizations.…”
Section: Dear Editormentioning
confidence: 99%
“…Authors suggested that multidisciplinary programs, as an excellent model, should be established in the other diabetic clinical settings around the world (15). In another study in Turkey, results showed that amputation rate due to DFU declined after implementation of a multidisciplinary team work (14). Also, in France the multidisciplinary consultation for patients with DFU proved effective not only in curative treatment, but also in primary and secondary prevention (16).…”
Section: Dear Editormentioning
confidence: 99%